1, 5‐Allyl Shift by a Sequential Achmatowicz/Oxonia‐Cope/Retro‐Achmatowicz Rearrangement. Issue 32 (24th June 2022) - Zhang, Xiayan; Tong, Yi; Li, Gang; Zhao, Hao; Chen, Guanye; Yao, Hongliang; Tong, Rongbiao
Abstract: 1, 3‐Allyl and 1, 2‐allyl shifts through [3, 3]‐ and [2, 3]‐sigmatropic rearrangements are well‐established and widely used in organic synthesis. In contrast, 1, 5‐allyl shift through related [3, 5]‐sigmatropic rearrangement is unknown because [3, 5]‐sigmatropic rearrangement is thermally Woodward–Hoffmann forbidden. Herein, we report an unexpected discovery of a formal 1, 5‐allyl shift of allyl furfuryl alcohol through a 2‐step sequential rearrangement. Mechanistically, this formal 1, 5‐allyl shift is achieved through a sequential ring expansion/contraction rearrangement: 1) Achmatowicz rearrangement (ring expansion), and 2) cascade oxonia‐Cope rearrangement/retro‐Achmatowicz rearrangement (ring contraction). This new 1, 5‐allyl shift method is demonstrated with >20 examples and expected to find applications in organic synthesis and materials chemistry. Abstract : An unexpected 1, 5‐allyl shift is discovered for allyl furfuryl alcohol through two‐step sequential ring expansion/contraction rearrangement at room temperature, which could be considered as a Woodward–Hoffmann‐forbidden formal [3, 5]‐sigmatropic rearrangement. Mechanistically, it involves Achmatowicz rearrangement, oxonia‐Cope rearrangement, and an unprecedented "retro‐Achmatowicz" rearrangement.